Proteoma do plasma seminal de touros da raça Gir - Leiteiro (Bos taurus indicus) clinicamente normais e com hipoplasia testicular - Cintia Liberia Faria Santos (2015)
The Gir - Dairy is an excellent option for dairy herds in Brazil because of the features presented by its animals, such as hardiness, adaptability and expressive milk production. Testicular hypoplasia causes reproductive problems in bulls and can lead to subfertility or, in more severe cases, infertility. In Brazil, the incidence of this disease varies from 5 to 15%. Due to the great importance that Gyr- Dairy animals have in the Brazilian cattle industry and because of the negative impact, not only in economically terms but also in fertility, caused by testicular hypoplasia, this study aimed to determine the differentially expressed protein profile between animals with this disease and clinically normal . Semen samples from 18 animals (9 hypoplastic and 9 normal) were collected and seminal plasma was centrifuged and subjected to two-dimensional electrophoresis (2-DE). Gels were stained with Coomassie Blue G-250, digitized and analyzed using PDQuest program 2-D Analysis Software to identify the "spots". Were identified 33 "spots" differentially expressed between the two groups of animals, 26 more intensely expressed in hypoplastic animals. The "spots" were cut from the gels and subjected to mass spectrometry and identified 38 proteins and, among these, the group of proteins known as Binder of Sperm Proteins (BSP) and platelet-activating factor acetylhydrolase (PAF - AH) were more present in spots identified in hypoplastic animals. The animals also underwent clinical and soundness evaluation and were statistical differences in the length, width and testicular volume, turbulence and sperm defects (p <0.05).